1999
DOI: 10.1038/sj.bjc.6690547
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and non-Hodgkin lymphoma in a cohort of older women

Abstract: SummaryWe investigated the relation of alcohol consumption to risk of non-Hodgkin's lymphoma (NHL) in a cohort of 35 156 lowa women aged 55-69 years who participated in the lowa Women's Health Study in 1986. Alcohol consumption at baseline was obtained using a mailed questionnaire. During the 9-year follow-up period, 143 incident cases of NHL were identified. Higher alcohol consumption was significantly associated with a decreased risk of NHL (P-trend = 0.03). Compared to non-drinkers, multivariate-adjusted re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 44 publications
7
40
3
Order By: Relevance
“…47 Similarly, the findings of the 2 other studies reporting an inverse association between alcohol intake and development of overall NHL were not based on European study populations, as one was a case-control study carried out in Japan 24 and the other one was a large American cohort study. 37 Our results reporting a protective effect of alcohol on development of NHL in countries like Ireland, Germany and Czech republic and the absence of such an effect in Mediterranean countries are consistent with findings from previous epidemiological studies revealing a protective effect of alcohol essentially in USA. Indeed, northern European countries and USA have a ''wet'' culture, where binge drinking is quiet common, while countries in Southern Europe have a ''dry'' culture, where drinking is an integral part of the diet and drinking for intoxication is rare.…”
Section: Discussionsupporting
confidence: 92%
“…47 Similarly, the findings of the 2 other studies reporting an inverse association between alcohol intake and development of overall NHL were not based on European study populations, as one was a case-control study carried out in Japan 24 and the other one was a large American cohort study. 37 Our results reporting a protective effect of alcohol on development of NHL in countries like Ireland, Germany and Czech republic and the absence of such an effect in Mediterranean countries are consistent with findings from previous epidemiological studies revealing a protective effect of alcohol essentially in USA. Indeed, northern European countries and USA have a ''wet'' culture, where binge drinking is quiet common, while countries in Southern Europe have a ''dry'' culture, where drinking is an integral part of the diet and drinking for intoxication is rare.…”
Section: Discussionsupporting
confidence: 92%
“…The present data are consistent with the general evidence on the issue, since of two cohort studies one found a direct (Kato et al, 1992) and one an inverse association (Chiu et al, 1999), and of four case -control studies one found a direct (De Stefani et al, 1998), one an inverse (Nelson et al, 1997) and two no appreciable association (Cartwright et al, 1988;Brown et al, 1992). Thus, they provide convincing evidence that alcohol drinkingmainly wine, even in relatively high amounts -is not appreciably related to the risk of lymphoid neoplasms.…”
Section: Discussionsupporting
confidence: 91%
“…This, however, may apply less to Italy, where alcohol drinking is widespread . Information on alcohol drinking was satisfactorily reproducible, as the Pearson correlation (Chiu et al, 1999), since also when the analysis was restricted to women, no significant association and no trend in risk were found for either total alcohol or wine intake. Moreover, as over 80% of this Italian population drunk wine frequently and in considerable amounts, our data support no appreciable association between NHL and wine drinking.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…368,369,373,374,376,382,388,[394][395][396][397][398][399] In a recent pooled analysis of 9 case-control studies, Morton et al 398 reported a significant inverse association with alcohol (pooled OR 5 0.83, 95% CI: 0.76-0.89), which did not vary with frequency or duration of intake, or by type of alcoholic beverage (OR for beer only, compared to nondrinkers 5 0.85, 95% CI: 0.76-0.95; OR for wine only 5 0.85, 95% CI: 0.74-0.99; OR for liquor only 5 0.90, 95% CI: 0.74-1.09). In a subgroup analysis of 4 of the studies with sufficient data, relative risk estimates were lower for current drinkers (pooled OR 5 0.73, 95% CI: 0.64-0.84) than for former drinkers (pooled OR 5 0.95, 95% CI: 0.80-1.14), compared to nondrinkers.…”
Section: Lifestyle and Personal Factors Tobacco And Alcohol Usementioning
confidence: 99%